O processo de estratégia em empresas agropecuárias: uma apreciação crítica - Pozzobon, Daniela Maria (2006)
This work presents a Methodology to the Formulation and Implementation of the Strategy Process in Farm Companies, and a critical appreciation of this process in the farm company. By means of this proposition we attempt to stand out the actual level of importance and recognition that farm companies represent as a powerful factor in economical promotion disclosed by the agribusiness thematic. This methodology of strategic administration, specific to the farm companies, tried to consider the strategy process characteristics found in the literature at the same time that it embodies the methodologies used by the farm companies which formed the corpus of this research as well as it is in accordance with the particular characteristics of this kind of company. Analyzing how rural producers formulate and establish their strategies, and according to the administration theory, these methodologies were discussed through a table of methodologies. This table contains the basic steps of strategic administration process, the steps enclosed in the methodologies proposed by the authors considered in the research, the steps of the methodologies used by the researched farm companies, the incremental techniques that these companies use specially in the context regarding the beginning of the Strategy Process and also the implementation of this Process. These made it possible to reach a more accurate identification of those steps that were the base to the Methodology of Formulation and Implementation of the Strategy Process in Farm Companies that this work proposes. Once this work is considered a case study in the category of multicase study, some data collecting procedures were used like interviews, documental analysis; direct observation and partake observation. The work is also characterized as exploratory regarding its objectives and qualitative considering its nature. In general terms, the key conclusion of this study was the shortage of the methodologies studied in the literature in opposition to what came out from the field research in relation to: (I) the matter of people preparation to the changes, (II) Company suitability, (III) shared formulation, (IV) strategy implementation and (V) a control based on budget and indexes, (VI) and moreover the link between strategic indexes and salary plan. Based on these results, the methodology presented in this work suggests as the first step in the process of Strategy Formulation what we call Preparation/Sensibilization. The second step is called Strategic Creativity that is simply the beginning of the strategy formulation. In the proposed methodology, the strategy begins with the formulation of the View of the company future. The third step corroborate in two parts (internal and external environment evaluation) with the common prescribed step sequence of the basic strategic process methodologies analyzed and it also includes a stage perceived in the field research, the evaluation of the actual performance of the company. This evaluation of the actual performance is the condition to grant the performance indexes formulation that is present in future steps of the process. The fourth step of the proposed methodology is the Formulation which includes the Budget creation, Macro-strategies, and indexes. The fifth step begins with the second important aspect of the strategy process as described by Andrews which is related to the formulation, the Implementation. At last, we have the Control stage. These six stages are compound of internal phases and are in a permanent feedback process. Finally, we can conclude that beyond the use of this specific methodology the farm companies need to recognize the presence of variable that they affect particularly in its external environment and that they influence the relationship directly enter the Strategic Process and the performance of the company. The presence of these external intervening variable characterizes the Farm Companies as of fragile, particular, unstable and perverse nature in the treatment of the Strategic Administration.